'I can say I was a journalist during a global pandemic': Australian students' experiences of a newsroom in lockdown. Issue 1 (1st June 2022) - McCarthy, Brigid; Bird, Dylan; Sherwood, Merryn; Zion, Lawrie
The COVID-19 pandemic presented university journalism educators with a dual challenge: transitioning subjects online and helping students navigate an industry that is experiencing disruption to work practices and job losses. The impact was particularly felt in practice-based subjects such as student newsrooms. While work-integrated learning programmes have become ubiquitous in journalism courses to produce job-ready graduates, the pandemic required educators to implement swift changes to accommodate online learning in them. The pandemic provides an opportunity to explore how students perceive the value of curriculum-related newsrooms during significant industry upheaval. Many studies have examined these practical journalism education programmes; however, the student perspective is often lacking. This case study, based on student questionnaire responses and educators' observations, chronicles the experiences of working remotely in a curriculum-related newsroom during the 2020 COVID-19 lockdowns. It situates this within Jaakkola's 'pedagogical newsroom' that blends pedagogical and journalistic principles to simulate practice within a flexible environment. Due to this flexibility, educators were able to adapt content for unanticipated online delivery to meet learning outcomes and even to create new learning opportunities. Student survey responses showed that despite the disruption, they believed the programme offered vital preparation for industry and generally remained optimistic about their career prospects.